2009
DOI: 10.1016/j.foodpol.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Farmer organization, collective action and market access in Meso-America

Abstract: The global agricultural economy is changing. Commodity prices are declining, and producers increasingly supply complex value chains. There is growing interest in how farmers can benefit from emerging market opportunities. Farmers are encouraged to produce high value crops and engage in value-adding activities such as agro-processing. Farmer organization and collective action are often seen as key factors in enhancing farmers' access to markets. Often too little attention is directed at a) the most appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
225
0
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(261 citation statements)
references
References 11 publications
6
225
0
14
Order By: Relevance
“…Many scholarly works (Vorst et al, 1998;Van der Vorst et al, 2007;Stank et al, 1999;Power, 2005;Mena & Stevens, 2010) identified the role of food supply chain management as a means of developing trustful partnerships in foods chains and the role of trust for effectiveness of supply chain management. A well-established supply chain management system has potential to improve benefit share among the chain actors and overall market performances (Hellin et al, 2009;Taylor, 2005). Similarly, some authors (Kummu et al, 2012;Lipinski et al, 2013) noted the role of supply chain management in reducing food losses in food value chains.…”
Section: Supply Chain Management In the Wheat Value Chainmentioning
confidence: 99%
“…Many scholarly works (Vorst et al, 1998;Van der Vorst et al, 2007;Stank et al, 1999;Power, 2005;Mena & Stevens, 2010) identified the role of food supply chain management as a means of developing trustful partnerships in foods chains and the role of trust for effectiveness of supply chain management. A well-established supply chain management system has potential to improve benefit share among the chain actors and overall market performances (Hellin et al, 2009;Taylor, 2005). Similarly, some authors (Kummu et al, 2012;Lipinski et al, 2013) noted the role of supply chain management in reducing food losses in food value chains.…”
Section: Supply Chain Management In the Wheat Value Chainmentioning
confidence: 99%
“…Hal ini bahkan telah menjadi faktor utama yang menyebabkan kegagalan pelaksanaan program secara keseluruhan (PSEKP, 2006). Banyak studi membuktikan bahwa tidak mudah membangun organisasi petani (Hellin et al, 2007), karena petani cenderung merasa lebih baik tidak berorgansiasi (Stockbridge et al, 2003).…”
Section: Abstrakunclassified
“…Pengorganisasian petani baik sebagai pembudidaya, pengolah, maupun pelaku pemasaran; membutuhkan pemahaman secara sosiologis yang mendalam yaitu keorganisasian seperti apa yang sesungguhnya sesuai bagi mereka. Menghadapi situasi ini, keterlibatan aparat pemerintah tampaknya harus dilakukan secara bijak dan menggunakan basis keilmuan yang cukup (Hellin et al, 2007).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Numerous studies have tried to assess the extent onto which cooperatives are inclusive (Bernard and Taffesse, 2012;Fischer and Qaim, 2012). For instance, it has been found that human and social capital is closely linked to the extent of membership in such organizations (Hellin et al, 2009;Karli et al, 2006;Francesconi and Heerink, 2010). Some authors point out that poor members are often disadvantaged due to their lack of essential assets such as education, organizational skills or financial capacity (Hulme and Shepherd, 2003).…”
Section: Introductionmentioning
confidence: 99%